2011
DOI: 10.1111/j.1600-051x.2011.01706.x
|View full text |Cite
|
Sign up to set email alerts
|

Salivary biomarkers of periodontal disease in response to treatment

Abstract: Background Salivary biomarkers of periodontitis were assessed longitudinally to determine response to therapy. Methods A 6-month case-controlled study of adults with chronic periodontitis was performed, with 33 participants receiving oral hygiene instructions (OHI) alone and 35 with scaling and root planing (SRP) combined with OHI. Saliva samples collected at week 0, 16 and 28 were analyzed for interleukin-1β (IL-1β), IL-8, macrophage inflammatory protein (MIP)-1α, matrix metalloproteinase-8 (MMP-8), osteopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
164
1
9

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(191 citation statements)
references
References 53 publications
(78 reference statements)
17
164
1
9
Order By: Relevance
“…Identifying biomarkers in the blood or other body fluids of an individual may aid in the diagnosis of disease and predict treatment outcomes in patients with HNSCC (3,4). In a cross-sectional study, analysis of a candidate biomarker uses single time-point sampling from population data (5). By contrast, a longitudinal analysis involves using multiple samples from a single patient at various time points; therefore, this type of analysis reveals quantitative alterations in the candidate biomarker in the patient, which may be associated with improved health, treatment outcomes and clinical status of the patient (6).…”
Section: Introductionmentioning
confidence: 99%
“…Identifying biomarkers in the blood or other body fluids of an individual may aid in the diagnosis of disease and predict treatment outcomes in patients with HNSCC (3,4). In a cross-sectional study, analysis of a candidate biomarker uses single time-point sampling from population data (5). By contrast, a longitudinal analysis involves using multiple samples from a single patient at various time points; therefore, this type of analysis reveals quantitative alterations in the candidate biomarker in the patient, which may be associated with improved health, treatment outcomes and clinical status of the patient (6).…”
Section: Introductionmentioning
confidence: 99%
“…IL-1β and TNF-α are is produced by a wide variety of cell types (macrophages, fibroblasts, keratinocytes, and PMNs leucocytes), but the primary producer of IL-1β in the gingival tissues is the macrophage. 4,5,[13][14][15][16][17] IL-1β has a number of biologic effects, including initiating the acute phase response to infection. However, in the periodontium, it likely functions to mediate connective tissue destruction and osteoclastic bone resorption.…”
Section: 22-26mentioning
confidence: 99%
“…Salivary levels of IL-1β, MMP-8, OPG, and MIP-1α refl ected disease severity and response to therapy suggesting their potential utility for monitoring periodontal disease status. [13][14][15][16][17] OPG used as a marker of bone turnover. [3][4][5]17 It can be concluded that the indicators of acute periodontitis can detect with β-glucuronidase and AST, IL-1β, and MMP-8, whereas indicators for chronic periodontitis can detect with ALP.…”
Section: 22-26mentioning
confidence: 99%
See 1 more Smart Citation
“…Também tem sido mostrado que a MMP-8 analisada pela técnica de ELISA diminui após o tratamento periodontal não cirúrgico, assim como no tratamento com doxyciclina (Sorsa, Ding et al 1994;Gorska and Nedzi-Gora 2006;Sexton, Lin et al 2011). …”
Section: Steunclassified